2015
DOI: 10.1136/archdischild-2014-307684
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes following late and moderate prematurity: a population-based cohort study

Abstract: ObjectiveThere is a paucity of data relating to neurodevelopmental outcomes in infants born late and moderately preterm (LMPT; 32+0–36+6 weeks). This paper present the results of a prospective, population-based study of 2-year outcomes following LMPT birth.Design1130 LMPT and 1255 term-born children were recruited at birth. At 2 years corrected age, parents completed a questionnaire to assess neurosensory (vision, hearing, motor) impairments and the Parent Report of Children's Abilities-Revised to identify cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
185
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(210 citation statements)
references
References 51 publications
17
185
1
7
Order By: Relevance
“…[2][3][4][5] These problems are evident in infancy and recent population-based studies have shown that children born LMPT are at twice the risk for neurodevelopmental disability compared with term-born controls at two years of age. [6] Developmental assessments in the early years are regarded as important for identifying children at risk and for targeting early intervention. [7,8] As such, developmental tests at two years are widely used to assess neurodevelopmental outcomes and to ascertain eligibility for intervention services.…”
mentioning
confidence: 99%
“…[2][3][4][5] These problems are evident in infancy and recent population-based studies have shown that children born LMPT are at twice the risk for neurodevelopmental disability compared with term-born controls at two years of age. [6] Developmental assessments in the early years are regarded as important for identifying children at risk and for targeting early intervention. [7,8] As such, developmental tests at two years are widely used to assess neurodevelopmental outcomes and to ascertain eligibility for intervention services.…”
mentioning
confidence: 99%
“…However, the study suggests that gestational age, low weight at birth and gender may be more influential in the long term in these children, thus being necessary to monitor this population -as has been observed in other studies reviewed (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) . These results evidenced the importance of monitoring these children from birth, although none of them followed-up on psychological factors such as those proposed by Kupfer et al (39) , indicated as closely related to language acquisition (40) .…”
Section: Discussionmentioning
confidence: 90%
“…Psychosocial aspects such as maternal mood, particularly maternal depression during the first six months after birth, were not associated with language abnormalities at 18 months according to the Bayley Scales (16) . In assessing performing functions and their relation to language, several studies indicated a positive correlation between attention abnormalities and other performing functions and poorer language performance (22,27) , having also related it to lower gestational age (27) and poorer nonverbal learning (27) . Premature children presented poorer performing functions (22) , although they are not different from full-term infants in terms of attention-deficit and hyperactivity disorder (21) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations